Issues of Artistic Skills in Siddiqi-Ajzi's Creation - Shaymardonov, Tilovmurod Abilaevich (Researchparks Publishing, 2023)
The political-legal, socio-economic, spiritual-educational views of the period, the state of ignorance of Turkestan, which is lagging behind the development, are artistically reflected in the works of Siddiqi Ajzi. It is shown that the poet's literary skill grew and improved along with the life of the society, and that artistically perfect works were inherited from him.